Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1179/oeh.2009.15.2.143
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the Incidence of Acute Pesticide Poisoning by Educating Farmers on Integrated Pest Management in South India

Abstract: Sixty-five farmers reported on pesticide use and the signs and symptoms of acute pesticide poisoning when using two different plant protection strategies: in 2003 using chemical controls and in 2004 using an approach to Integrated Pest Management (IPM) based on an ecological analysis of the field conditions. Exposure to organophosphates was confirmed as a serious risk factor for occupational poisoning. The adoption of IPM reduced the use of pesticides and halved the incidence of acute pesticide poisoning. Over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 21 publications
1
32
0
2
Order By: Relevance
“…The effective education programmes regarding pesticide safety could be useful in preventing pesticide poisoning 14. Previous studies have suggested that pesticide safety education among farmers could raise awareness of pesticide exposure risk16 and the adverse health consequences associated with acute pesticide poisoning 17. Improvements in pesticide safety knowledge using different delivery modes may lead to some improvement in protective practices18 and increase the use of personal protective equipment 19.…”
Section: Discussionmentioning
confidence: 99%
“…The effective education programmes regarding pesticide safety could be useful in preventing pesticide poisoning 14. Previous studies have suggested that pesticide safety education among farmers could raise awareness of pesticide exposure risk16 and the adverse health consequences associated with acute pesticide poisoning 17. Improvements in pesticide safety knowledge using different delivery modes may lead to some improvement in protective practices18 and increase the use of personal protective equipment 19.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that pesticide safety education among farmers could raise awareness of both pesticide exposure risk [19] and the adverse health consequences associated with acute pesticide poisoning [20]. Improvements in pesticide safety knowledge using different delivery modes may lead to some improvement in protective practices [21] and increase the use of personal protective equipment [22].…”
Section: Discussionmentioning
confidence: 99%
“…Most signs and symptoms of diazinon toxicity are related to cholinergic manifestation, which is mediated through the inhibition of serum AChE activity. Toxicity increases when the reduction reaches 50% or more in enzyme activity [17]. In the present case, the blood sample was hemolyzed and, therefore, was not eligible for serum AChE activity analysis by a colorimetric method that could be utilized as a confirmatory test for organophosphorus poisoning.…”
Section: Discussionmentioning
confidence: 94%